Is the Tendency to Free Ride Impacting Your Willingness to Pay for Public Healthcare - Proniewicz, Justyna Ewa (Central European Journal of Economic Modelling and Econometrics, 2023)
Healthcare services differ from other public goods due to the characteristics of their demand and supply. As a public good, its provision might allow for a free rider effect. This study aimed at checking whether a patient’s overall tendency to free ride impacts the Willingness to Pay for public healthcare access. The study demonstrates that besides the experience level with the valued good, free riding tendency also influenced the valuation. The results indicate that not only past decisions about free riding but also readiness to free ride in the future might change the willingness to pay for the public good.